Current Laboratory Instrumental Methods for Detecting Environmental Radioactivity - Melgard, R.; Rodgers, D. (IEEE transactions on nuclear science, 1982)
The composite technologies required to provide data on environmental radioactivity encompass the following specialties: · Radiochemistry · Radiation Physics · Radiation detectors · Computer systems and programming · Quality Control/Quality Assurance · Regulations · A black-box understanding of electronics sufficient to package the technologies into a useful system. This paper concentrates on "Laboratory Instrumental Methods" and touches on other subjects only insofar as they are applied directly to this subject. As a treatise on instrumental methods the emphasis is on a practical application of available technologies in a modern analytical laboratory. Radiation physics is mentioned from the reference frame of a laboratory analyst as a prelude to the specific topics of instrumentation, calibration, sensitivity, quality control and data processing.